2010
DOI: 10.1016/j.toxicon.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

A new tick Kunitz type inhibitor, Amblyomin-X, induces tumor cell death by modulating genes related to the cell cycle and targeting the ubiquitin-proteasome system

Abstract: The aim of this study was to evaluate the anti-tumor activity of Amblyomin-X, a serine protease Kunitz-type inhibitor. Amblyomin-X induced tumor mass regression and decreased number of metastatic events in a B16F10 murine melanoma model. Alterations on expression of several genes related to cell cycle were observed when two tumor cell lines were treated with Amblyomin-X. PSMB2, which encodes a proteasome subunit, was differentially expressed, in agreement to inhibition of proteasomal activity in both cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 29 publications
2
56
0
9
Order By: Relevance
“…Investigations have included studies on anti‐tumoral effects (Chudzinski‐Tavassi et al ., 2010; Abreu et al ., 2014; Sousa et al ., 2015), applications against inflammatory diseases like myasthenia gravis (Hepburn et al ., 2007), new anticoagulants (Koh et al ., 2011) and the treatment of asthma (Horka et al ., 2012). …”
Section: Tick Saliva As a Source Of Toxins Tick‐borne Pathogens And mentioning
confidence: 99%
“…Investigations have included studies on anti‐tumoral effects (Chudzinski‐Tavassi et al ., 2010; Abreu et al ., 2014; Sousa et al ., 2015), applications against inflammatory diseases like myasthenia gravis (Hepburn et al ., 2007), new anticoagulants (Koh et al ., 2011) and the treatment of asthma (Horka et al ., 2012). …”
Section: Tick Saliva As a Source Of Toxins Tick‐borne Pathogens And mentioning
confidence: 99%
“…In other tumor cell lines (SK-Mel-28, MiaPaca-2, RENCA), Amblyomin-X has been demonstrated to show these same effects associated with pro-apoptotic stimuli that involve mainly through proteasome inhibition, imbalance between pro-and anti-apoptotic Bcl-2 family proteins, mitochondrial dysfunction, production of reactive oxygen species, caspase cascade activation, and ER-stress [16,17]. Additional studies in B16F10 cells are planned to clarify these questions.…”
Section: Discussionmentioning
confidence: 95%
“…AAT68575) identified in the transcriptome of the salivary glands of the Amblyomma cajennense tick [14,15]. The studies performed with Amblyomin-X have shown that this is also able to induce cell cycle arrest and apoptosis in different tumor cell lines, and in vivo experiments, it promotes regression and reduction of metastases of some tested tumors [16,17]. This study demonstrated that Amblyomin-X and heparin have similar effects on cancer progression and on the normalization of the hypercoagulable state, but that in vitro, Amblyomin-X has a clearly distinct mechanism in triggering its effects, because in cancer cells, it exerts a cytotoxic effect leading to apoptosis and cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant gliomas are aggressive cancers and refractory to therapy so that Ixolaris provides a potential treatment inhibiting tumour growth, angiogenesis and and metastasis (Carneiro-Lobo et al, 2009). Likewise, Amblyomin X, from the hard tick, Amblyomma cajennense, targets melanoma cells, inducing apoptosis and tumour regression (Chudzinski-Tavassi et al, 2010).…”
Section: Therapeutic Development Of Salivary Gland Componentsmentioning
confidence: 99%